Implemetasi Penguatan Karakter Disiplin Melalui Kegiatan Islamyah - Rahman Hakim, Arif; Mahali, Jalal (ILJ: Islamic Learning Journal, 2025)
This research explores how Islamic activities are implemented to reinforce students’ discipline character at MI Thoyib Hidayat. Using a qualitative descriptive approach, data were obtained through observation, interviews, and documentation involving the principal, teachers, and students. The study finds that discipline is cultivated through regular religious practices such as Qur’an recitation, tahfidz, shalat dhuha, congregational prayers, istighotsah, and maintaining cleanliness and order. These activities integrate aspects of faith, worship, and morality into students’ learning and daily conduct. Teachers serve as key role models, mentors, and supervisors in ensuring program effectiveness. Despite challenges such as inconsistent student discipline, diverse family backgrounds, and limited resources, the school addresses them through consistent rule enforcement, teacher exemplification, parental collaboration, and continuous habituation.